Dynamic Capabilities and Hospital Performance: Perception Study of the NU Hospital Directors in East Java - Saiful Anam; Soegeng Sutejo; Muhammad Nafik Hadi Ryandono (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2023)
There is a lot of empirical evidence regarding the effect of financial resources, entrepreneurial orientation, and information technology on dynamic capabilities and firm performance. So it is necessary to reconcile these findings. The analytical tool used in this research is (SmartPLS) version 3.0. Population in this study are individuals who work, have leadership-level positions or are directors of NU hospitals in East Java. The number of NU hospitals in the East Java region is 22 hospitals. The sample size obtained is a minimum of 57 individuals. The results of this study are financial resources are empirically proven to have a direct effect on dynamic capabilities, and financial resources also have an indirect influence on hospital performance through dynamic capabilities, entrepreneurial orientation is empirically proven to have a direct effect on dynamic capabilities, and entrepreneurial orientation on hospital performance. Through dynamic capabilities, financial resources have not been empirically proven to have a direct effect on dynamic capabilities, dynamic capabilities do not mediate the relationship between financial resources and hospital performance, and dynamic capabilities have a direct effect on hospital performance